Clinical relevance of enteropathogen co-infections in preschool children—a population-based repeated cross-sectional study. (August 2019) - Pijnacker, R.; van Pelt, W.; Vennema, H.; Kortbeek, L.M.; Notermans, D.W.; Franz, E.; Mughini-Gras, L.
Abstract: Objectives: This study aimed to (i) determine risk factors for enteropathogen co-infections, (ii) determine whether enteropathogen co-infections influence gastroenteritis risk, and (iii) determine whether enteropathogen co-infection occurred randomly in preschool children. Methods: A monthly-repeated cross-sectional survey in Dutch children aged 0–48 months was conducted during October 2012 to October 2014. A total of 981 stool samples were collected along with questionnaires collecting data on gastrointestinal symptoms and potential risk factors; 822 samples were successfully tested for 19 enteropathogens using real-time multiplex PCRs. Logistic regression analysis assessed co-infections in relation to gastroenteritis and potential risk factors. Results: In all, 598/822 (72.7%) stool samples tested positive for at least one enteropathogen, of which 290 (48.5%) were positive for two or more enteropathogens. Risk factors for two or more enteropathogen co-infections were young age (<12 months, OR 1.9, 95% CI 1.1–3.3; 13–36 months, OR 1.7, 95% CI 1.1–2.5, versus 37–48 months), day-care attendance (OR 1.8, 95% CI 1.3–2.5), households with three or more children versus those with one child (OR 1.7, 95% CI 1.1–2.8). Stool samples collected in spring less often had two or more enteropathogens versus summer (OR 0.4, 95% CI 0.2–0.7). Food allergy was a risk factor for three or more enteropathogen co-infections (OR 3.2, 95% CI 1.1–8.9). The frequency of co-infection was higher than expected for norovirus GI/norovirus GII, Clostridium difficile/ norovirus GI, C. difficile /rotavirus, astrovirus/ Dientamoeba fragilis, atypical enteropathogenic Escherichia coli /adenovirus, typical enteropathogenic E. coli /adenovirus, and enteroaggregative E. coli /astrovirus. No co-infection was associated with increased gastroenteritis risk. Conclusions: Risk factors for enteropathogen co-infections were identified and specific enteropathogens co-occurred significantly more often than expected by chance. Enteropathogen co-infections were not associated with increased gastroenteritis risk, calling into question their clinical relevance in preschool children.